Enkele opmerkinge oor die gewete - Heyns, Johan Adam (Verbum et ecclesia, 1993)
Some remarks on conscience The phenomenon of the human conscience has been not only the object of penetrating analysis through the centuries, but also a highly abused human faculty. The question can be asked: is conscience concerned only with man’s relation to himself, or also with man’s relation to Cod and to other men and even to institutions such as the state and the church? To certain people conscience pretends to be the voice of God within them and therefore the standard for the relation to other men. But in this case man himself became God.